DESIGNING AN INVENTORY MODEL FOR THE BEHAVIOR OF DEPENDENCE ON LPG GAS CONSUMPTION OF 3 KG USING THE DYNAMIC SYSTEM SIMULATION METHOD IN LUWUK BANGGAI REGENCY - Izzul Aziz; Abdul Mail; Muhammad Nusran; Anis Saleh; Dirgahayu Lantara; Nurhayati Rauf; Muhammad Fachry Hafid (Center for Study and Journal Management FTI UMI, 2022)
Liquefied Petroleum Gas (LPG) or more commonly known as LPG gas is a gas stove fuel that comes from the results of liquefied petroleum gas and is then put into a tube, one of which is a 3-kilogram tube. The behavior of dependence on the consumption of 3-kilogram gas cylinders from the people of Banggai Regency can be seen from the use of non-subsidized 3 kilogram LPG gas, namely (±) 32. 002 people/group, the second is the consumption rate from subsidies and non-subsidies, namely 38. 864 units from total users, namely (±) 45. 000 people/groups with a supply of 30. 800 units and the third about frequent scarcity in 2020 and early 2021 reported by Banggai News and Obormotindok. Simulation Method Dynamic systems are modeling and running simulations of real systems to analyze problems and present solutions from policy scenarios from the researcher's perspective. By using this method, researchers can identify the behavior of 3 kilograms of gas consumption from the rate of consumption and demand through tables and graphs using the Powersim Studio 7 software. The results of the study present 3 policy scenarios, namely the first scenario regarding an increase in the transition to 99% non-subsidized gas cylinders with simulation results, namely September 1 2021 - October 1 2022 the demand is fulfilled, the second scenario regarding the addition of a 7th agent with simulation results, namely September 1 2021 - April 1 2023 demand can still be fulfilled and the third scenario regarding an increase in the transition to 99% non-subsidized gas cylinders and the addition of a 7th agent with simulation results, namely 1 September 2021 – 1 September 2023 the demand for needs is fulfilled. The conclusion is that the third policy scenario will be taken because among the policy scenarios presented, the preparation of tube supplies is fulfilled within two years, namely September 1 2021 - September 1 2023.